Analisis Nikah Poligami Ditinjau dari Hukum Islam (Syarat Yang Ketat dan dalam Keadaan Tertentu) - ahmad yofi alfatikh (HOKI : Journal of Islamic Family Law, 2024)
In principle, in Islam there is the ability to practice polygamy, but absolute conditions apply to a husband. This absolute requirement is the ability to marry only 4 wives and to be able to treat his wives fairly. If the conditions that apply to adi cannot be fulfilled by a husband, then he is obliged to marry only one wife. Provisions regarding polygamy in Indonesia have been regulated in Law no. 1 of 1974 concerning Marriage, and as a form of positive response to regulate a husband who wants to marry more than one person. Likewise, the Compilation of Islamic Law regulates polygamy provisions and conditions for practicing polygamy for Muslims. Ideally, both regulations - Law no. 1/1974 and KHI--aims to provide provisions and requirements for husbands who wish to remarry (polygamy). These provisions aim to at least minimize abusive attitudes on the part of husbands (men) towards wives (women). This is also for the sake of creating a family that is sakinah, mawaddah and rahmah.